Formulation and Evaluation of Self‑emulsifying Drug Delivery System of Bosentan (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The objective of the present study was to develop self-emulsifying drug delivery system (SEDDS) of bosentan to improve its solubility, in vitro dissolution efficiencies, and further the bioavailability. Materials and Methods: The solubility of bosentan in various oils, surfactants, and cosurfactants was determined. Pseudoternary phase diagrams were constructed using Gelucire 44/14, Cremophor EL, and polyethylene glycol 400 (PEG 400) to identify the efficient self-microemulsification region. Prepared SEDDS was evaluated for emulsification time, drug content, optical clarity, droplet size, zeta potential, and in vitro dissolution. Results and Discussion: The optimized formulation FF5 had shown the smallest particle size, maximum solubility, less emulsification time, good optical clarity drug stability in water, and improved in vitro release. In the present study, already existed historical data were used for importing data. In the present study already existed historical data was used for importing data. Optimized SEDDS bosentan oral formulation (FF5) prepared had shown improved in vitro release when compared to commercial formulation. Conclusion: It was concluded that SEDDS would be a promising drug delivery system for poorly water-soluble drugs through oral route.